INFLUENCE OF HERBICIDAL NORMS ON CEREAL YIELD WHILE SOWING ON CORN FIELDS - Muminovna , Turdiyeva Nilufar; Kobiljonovna, Sayfullaeva Nazokat; Tursunov, Sotivoldi; Fakhriddin kizi, Sharafiddinova Mahliyo (International Journal of Psychosocial Rehabilitation, 2020)
The increase in grain production in Uzbekistan should be provided, first, by increasing productivity. To do this, use all available reserves. In the conditions of modern intensive agriculture, weed control is one of the most important elements of the agricultural system, on which the increase in crop productivity depends. With repeated sowing of leguminous crops in Uzbekistan, the number of crops grown will increase, the fertility of the land will increase, and environmental problems will be found. For this reason, from the group of scientists of the scientific research institute for plant protection, scientific work and experiments are carried out with the aim of destroying extraneous plants that are found among corn crops.